A blacksmith's tale: use of a rare earth magnet to facilitate safe removal of a metallic fragment from the face. Issue 10 (December 2020) - Radia, R.; Suffern, R.; Pepper, T.; Fan, K.
Abstract: A 48-year-old blacksmith presented to A&E after sustaining facial injuries while operating a metal punch press. Radiographs revealed the presence of a metallic foreign body within the cheek, but this was clinically impalpable. By using a neodymium rare earth magnet extraorally, it was possible to identify the position of the fragment several centimetres lateral to the entry wound. Triangulation of the fragment's position allowed retrieval under local anaesthetic through the original penetration wound, without need for cross sectional imaging or extensive exploration under general anaesthetic. This case highlights an application for magnets in detection and removal of impalpable metallic foreign bodies embedded in superficial soft tissues.